2002
DOI: 10.1002/ana.10292
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with simvastatin in normocholesterolemic patients with Alzheimer's disease: A 26‐week randomized, placebo‐controlled, double‐blind trial

Abstract: In a randomized, placebo-controlled, double-blind study, we investigated whether statins alter cholesterol metabolites and reduce Abeta levels in the cerebrospinal fluid of 44 patients with Alzheimer's disease. Individuals were given up to 80mg simvastatin daily or placebo for 26 weeks. Overall, simvastatin did not significantly alter cerebrospinal fluid levels of Abeta40 and Abeta42. In post hoc analysis, simvastatin significantly decreased Abeta40 levels in the cerebrospinal fluid of patients with mild Alzhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
257
5
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 389 publications
(278 citation statements)
references
References 18 publications
9
257
5
7
Order By: Relevance
“…Sjogren et al (2003) observed reduced CSF ␣-and ␤-sAPP levels after 12 weeks of simvastatin therapy. Moreover, statin use has been correlated with a reduction in serum and CSF A␤ levels and brain hydroxycholesterol levels (Buxbaum et al, 2002;Simons et al, 2002). It has been argued that the basis of these effects is the dependence of APP processing on neuronal membrane cholesterol content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sjogren et al (2003) observed reduced CSF ␣-and ␤-sAPP levels after 12 weeks of simvastatin therapy. Moreover, statin use has been correlated with a reduction in serum and CSF A␤ levels and brain hydroxycholesterol levels (Buxbaum et al, 2002;Simons et al, 2002). It has been argued that the basis of these effects is the dependence of APP processing on neuronal membrane cholesterol content.…”
Section: Discussionmentioning
confidence: 99%
“…Statin treatment has been shown to reduce A␤ production both in vitro and in animal models (Fassbender et al, 2001;Petanceska et al, 2002;Parvathy et al, 2004). Recent prospective studies indicate that statin use reduces soluble A␤ levels in the brain and may improve cognitive function (Buxbaum et al, 2002;Simons et al, 2002;Sjogren et al, 2003;Caballero and Nahata, 2004). These effects are thought to result from reduction in amyloidgenic amyloid precursor protein (APP) processing owing to the sensitivity of ␤ and ␥ secretases to neuronal membrane cholesterol content (Simons et al, 1998;Kojro et al, 2001;Burns and Duff, 2002;Wahrle et al, 2002;Wolozin, 2002;Cordy et al, 2003;Puglielli et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] All had placebo rather than standard care comparators. RCTs (reported in 23 publications [13][14][15][36][37][38][39][40][41][42][43][44][45][46][47][48][50][51][52]55,56,62,64 ) enrolled subjects with normal cognition at baseline, four RCTs (reported in seven publications 12,54,[57][58][59][60][61] ) enrolled patients with AD, and three RCTs enrolled other cognitively impaired subjects (traumatic brain injury, 53,63 and neurofibromatosis type 1 49 ). Simvastatin (eight trials), pravastatin (eight trials), and lovastatin (six trials) were most frequently utilized in the statin RCTs.…”
Section: Assessment Of Heterogeneity and Meta-regression Analysesmentioning
confidence: 99%
“…In addition to the cholesterol lowering effect, statins have many pleiotropic effects, such as reducing Aβ production, suppressing inflammatory responses, protecting neurons from excitotoxins, apoptosis, and oxidative stresses, and promoting synaptogenesis [16][17][18][19] . In particular, statins have been linked to the reduced prevalence of AD in statin-prescribed populations [20,21] , the improved cognition in normo-cholesterolemic patients [22] , and the slowed cognitive decline in mild-to-moderate AD patients [23] . It has been shown that simvastatin was effective in reversing learning and memory deficits in an aged AD mouse model [24] .…”
Section: Introductionmentioning
confidence: 99%